Pengaruh Media Pembelajaran Wordwall Terhadap Minat Belajar Mata Pelajaran IPAS Siswa Kelas V Sekolah Dasar - Israwaty, Ila; Amran, Muhammad; Fadilah, Nurul (Universtas Negeri Makassar, 2025)
This study aims to describe and analyze the effect of the use of Wordwall learning media on interest in learning science in class V UPTD SD Negeri 12 Parepare. Quasi-experimental design with Nonequivalent Control Group Design model. The sample consisted of 40 students consisting of experimental group and control group, Information collection through interest questionnaire instrument. The research findings showed that the average score of the experimental class reached 82.75, exceeding the achievement of the control class of 72.40. The results of the inferential analysis through the Independent Sample T-Test analysis obtained a Sig (2-tailed) value of 0.001, < 0.05, so that H0 was rejected and H1 was accepted with effect sizes of 1,323. Based on these results, it can be concluded that the use of Wordwall learning media has a significant and effective effect in increasing interest in learning science subjects in class V UPTD SD Negeri 12 Parepare.